2018
DOI: 10.1017/cem.2018.57
|View full text |Cite
|
Sign up to set email alerts
|

System outcomes associated with a pediatric emergency department clinical decision unit

Abstract: CLINICIAN'S CAPSULE What is known about the topic? Clinical decision units (CDUs) may reduce short-stay hospitalizations (<48 hours), which are associated with longer lengths of stay, increased staffing needs and higher costs. What did this study ask? What are the disposition outcomes and emergency department (ED) return rates following CDU care? Has CDU implementation changed short-stay hospitalization rates? What did this study find? Most CDU patients were discharged, and short-stay hospitalization rate sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, it has also been suggested that the introduction of the 4-hour target has increased (short-duration) admission rates, but consistent data are lacking 3. This leads to the discussion of a possible role of short-stay units, as these can potentially reduce ED length of stay as well as admissions 34…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been suggested that the introduction of the 4-hour target has increased (short-duration) admission rates, but consistent data are lacking 3. This leads to the discussion of a possible role of short-stay units, as these can potentially reduce ED length of stay as well as admissions 34…”
Section: Discussionmentioning
confidence: 99%
“…This extended evaluation can determine which illnesses/injuries are more serious and may require hospital admission [26]. The impact of the implementation of an observation unit on hospital admissions is studied and described in two primary studies and two systematic literature reviews [6,11,12,25].…”
Section: Resultsmentioning
confidence: 99%
“…In the more recent study by Karacabeyli et al . [12], a four-bed observation unit was integrated next to a PED (24/7 open and staffed by a nurse and nurse practitioner). The short-stay hospitalisation rate (<48 h) fell from 3.62% before the implementation of an observation unit to 3.23% after the implementation ( P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation